Nigerian economic review (Ikeja, Nigeria : John West Publications, 1986)
This publication provides a review of the Nigerian economy covering the period January 1984 to December 31, 1985. It covers topics and sectors that include: counter trade; monetary and fiscal policies; wages, prices and incomes; taxation; employment; agriculture; commerce and industry; oil sector; external trade; public debt; federal government budget; state government budget; and economic statistics.
lje 5/3/19
Arch
Keywords: Economic conditions; Economic history-Nigeria; Nigeria